Health service utilization, among Bangladeshi migrant workers in Malaysia - Uddin, Md. Sayed (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
The present work is an empirical study of Bangladeshi workers' use of healthcare services in Malaysia. It is guided by Andersen's (1968, 1995) Behavioural Model of population characteristics frameworks that consist of three factors that predispose services use (e.g. demographic), enabling use (financial resources) and need for care. The study also investigates the barriers that Bangladeshi temporary workers perceive to prevent their access to healthcare services. It further assesses their present health status in Malaysia and factors affecting their health. A questionnaire was administered to 300 respondents involved in construction, manufacturing and services sectors. The study employed two statistical methods. First, Chi-square test was used to find the significant association among variables. Second, binary logistic regression analysis was used to test the hypotheses. The key finding indicates that Bangladeshi workers' education level is a strong significant predictor of maintaining sound health condition in Malaysia. In contrast, their health deteriorates because of long duration of stay in Malaysia. This study reveals that many Bangladeshi workers (n-212) are not consistent in visiting doctors, hospitals or clinics and emergency rooms when they experience sickness in the past one year. The reason is that the majority of them (n=131) were found to practicse self-treatment or self-medication to overcome various illnesses. Further, the majority of the workers do not get any medical facility from their employers. The theoretical implication of Andersen's behavioural model is that predisposing and need factors are found significantly and positively associated with the use or visit to doctors, hospitals or clinics in one year. The findings reveal that predisposing factors, including age and marital status; and need factors, including self-rated health status, suffering chronic illnesses in the previous one year, have the greatest impact on healthcare utilization. Bangladeshi workers' who are married and have better health condition, suffer from chronic illnesses in the last one year were more likely to use healthcare services. It is also found that the Andersen's model is most useful for predicting doctor, hospital or clinic visits in one year. However, Andersen's behavioural model for Bangladeshi migrant workers was not a good framework for use or visit to emergency rooms and overnight stay at the hospital. The major findings indicate that healthcare providers do not understand workers' problems, high medical costs, self-treatment and lack of transportation which are the primary barriers for the majority of respondents from using healthcare services. According to binary logistic regression analysis, there is no statistical significance for the relationship between education, duration of stay in Malaysia and workers' involvement in three working sectors with any types of healthcare services utilization. Finally, the study suggests that adequate measure should be taken to provide pre-departure training related to existing healthcare system in Malaysia including existing health insurance coverage and extension of services to the expected migrant workers.